1992
DOI: 10.1152/jappl.1992.72.4.1480
|View full text |Cite
|
Sign up to set email alerts
|

Role of glutamate as the central neurotransmitter in the hypoxic ventilatory response

Abstract: Recent data suggest that the increase in ventilation during hypoxia may be related to the release of the excitatory amino acid neurotransmitter glutamate centrally. To further investigate this, we studied the effects of MK-801, a selective noncompetitive N-methyl-D-aspartate receptor antagonist, on the hypoxic ventilatory response in lightly anesthetized spontaneously breathing intact dogs. The cardiopulmonary effects of sequential ventriculocisternal perfusion (VCP) at the rate of 1 ml/min with mock cerebrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 0 publications
4
31
0
Order By: Relevance
“…N-methyl D-aspartate glutamate receptors in the nucleus of the solitary tract have a pivotal role in the hypoxic ventilatory response. 12 Preterm infants exhibit a biphasic ventilatory response. 13 There is an initial increase in ventilation for approximately 1 min.…”
Section: Peripheral Chemoreceptors and Impaired Hypoxic Ventilatory Rmentioning
confidence: 99%
“…N-methyl D-aspartate glutamate receptors in the nucleus of the solitary tract have a pivotal role in the hypoxic ventilatory response. 12 Preterm infants exhibit a biphasic ventilatory response. 13 There is an initial increase in ventilation for approximately 1 min.…”
Section: Peripheral Chemoreceptors and Impaired Hypoxic Ventilatory Rmentioning
confidence: 99%
“…12,13,24,27 For the current study, however, we selected dextromethorphan (DM) over MK-801 because preliminary studies in our lab demonstrated that low doses of MK-801 (0.1 ± 0.5 mgakg, i.p.) produced restlessness and hyperlocomotion in Z rats, while higher doses of MK-801 (1 ± 5 mgakg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…The AA solution used in this study contained proportionally more excitatory AA such as glutamate and aspartate than inhibitory AA such as glycine. which may also have an influence on the ventilatory response to hypoxia (5,30,31). Furthermore, the fact that this AA solution docs not contain GABA, an important inhibitory ncurotransmitter, may facilitate the effects of excitatory AA on the central respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these changes may be mediated by the increase and/or decrease in inhibitory or excitatory neurotransmitters in the CNS (4,10). One of the latter is glutamate, a central excitatory neurotransmitter that participates in the ventilatory response to hypoxia (5). Other AA that are not neurotransmitters may also influence the central respiratory output.…”
mentioning
confidence: 99%